2008
DOI: 10.1177/1088357608314899
|View full text |Cite
|
Sign up to set email alerts
|

Using a Three-Step Decoding Strategy With Constant Time Delay to Teach Word Reading to Students With Mild and Moderate Mental Retardation

Abstract: The use of a three-step decoding strategy with constant time delay for teaching decoding and word reading to students with mild and moderate mental retardation was investigated in this study. A multiple probe design was used to examine the percentage of words correctly decoded and read as well as the percentage of sounds correctly decoded. The data indicate that all five students learned to read words using the three-step decoding strategy with constant time delay. This was replicated with increased learning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…While this is at odds with broader understanding of reading instruction (Al Otaiba & Hosp, 2004;Cohen, Heller, Alberto & Fredrick, 2008), many children with Down syndrome have a relative strength in visual learning and in sight-word learning (Fidler et al, 2005). However, although a strength in visual and sight-word learning is a positive finding (and word recognition is one important element of the reading system as discussed earlier), there is a problem if we respond to this positive finding by limiting learning opportunities.…”
Section: Phonological Awareness and Phonic Decoding Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…While this is at odds with broader understanding of reading instruction (Al Otaiba & Hosp, 2004;Cohen, Heller, Alberto & Fredrick, 2008), many children with Down syndrome have a relative strength in visual learning and in sight-word learning (Fidler et al, 2005). However, although a strength in visual and sight-word learning is a positive finding (and word recognition is one important element of the reading system as discussed earlier), there is a problem if we respond to this positive finding by limiting learning opportunities.…”
Section: Phonological Awareness and Phonic Decoding Skillsmentioning
confidence: 99%
“…It is common for people with Down syndrome to have limited auditory short-term memory spans (Jarrold & Baddeley, 2001;Laws, 2002), and phonic decoding does utilise auditory short-term memory (Cohen et al, 2008). However, research provides evidence that even children who do not have a measurable auditory short-term memory span (thus a span of less than 1) can develop PA and phonic decoding skills (Cologon, Cupples & Wyver, 2011;Cohen et al, 2008;Cupples & Iacono, 2002). Furthermore, research evidence shows that reading development can improve auditory short-term memory in children with Down syndrome (Laws et al, 1995).…”
Section: Pa and Phonic Decoding Skills In Children With Down Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Settings varied across studies with five groups of researchers (Bradford et al, 2006;Browder et al, 2012;Finnegan, 2012;Flores et al, 2004;Fredrick et al, 2013) evaluating interventions within the participants' classroom (i.e., self-contained classroom). Two studies (Joseph, 2002;Cohen et al, 2008) reported providing interventions to participants outside of their special education classroom in alternate classrooms away from peers. Researchers for the remaining four studies (Allor, Mathes, Roberts, Cheatham, et al, 2010;Allor, Mathes, Roberts, Jones, et al, 2010;Conners et al, 2006;Waugh et al, 2009) did not explicitly report the location of intervention delivery.…”
Section: Participants and Settingsmentioning
confidence: 99%
“…The remaining four studies (Frederick et al, 2013;Joseph, 2002;Cohen et al, 2008;Waugh et al, 2009) in this review consisted of trained personnel implementing systematic explicit instruction. However, in three of the four studies (Joseph, 2002;Cohen et al, 2008;Waugh et al, 2009), the authors also incorporated simultaneous prompting within their respective interventions. Simultaneous prompting is an instructional strategy frequently used to teach students with ID various discrete skills in more traditional instructional formats (Riesen, et al, 2003).…”
Section: Prompting Proceduresmentioning
confidence: 99%